2021
DOI: 10.1111/jan.14766
|View full text |Cite
|
Sign up to set email alerts
|

The expression and receipt of compassion through touch in a health setting; a qualitative study

Abstract: Aim To investigate and understand how compassion is expressed by nurses and received by patients in a hospital setting. Background Concerns regarding the absence of compassion in a healthcare setting has necessitated further research in the field. To define and measure compassion is difficult and problematic. Compassion is subjective and in the contemporary literature the views of patients are under‐represented. Touch is an important component of nursing practice and can also be considered problematic. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Three sources in this review included perceptions of touch from both the nurse and the patient. 17 , 23 , 40 Gleeson and Timmins included articles on both the patient and nurse perception of both instrumental and expressive touch in the older adult mental health population. Findings indicated that patients perceived the nurses’ touch as a display of affection that caused comfort.…”
Section: Resultsmentioning
confidence: 99%
“…Three sources in this review included perceptions of touch from both the nurse and the patient. 17 , 23 , 40 Gleeson and Timmins included articles on both the patient and nurse perception of both instrumental and expressive touch in the older adult mental health population. Findings indicated that patients perceived the nurses’ touch as a display of affection that caused comfort.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies highlight the importance of touch in the experience of compassion, 26 safety, authenticity and connection. 30 One study explored how doctors communicate compassion by developing a taxonomy of compassionate physician behaviours in the realm of oncology. 31 Analyses suggested that the recognition of the patient's suffering, emotional resonance, and movement towards addressing suffering were all important elements in compassion interactions.…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies suggest effective communication, 25 interpersonal connections, 26,27 understanding, 28 being present, empathizing, 26 taking action and providing individualized care 29 are important to the experience of compassion. Other studies highlight the importance of touch in the experience of compassion, 26 safety, authenticity and connection 30 . One study explored how doctors communicate compassion by developing a taxonomy of compassionate physician behaviours in the realm of oncology 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients receive compassion through the touch of the nurse and this touch conveys comfort and safety. 15 Compassion has been defined as "the sensitivity to understand another person's suffering, the willingness and encouragement of one's well-being and help". 16 Watson stated that compassion plays a very important role in care.…”
mentioning
confidence: 99%